The Effect of profitability, solvency, audit committee, and audit quality on audit delay - Amalia, Rizka; Yusuf, Paulus Sugianto (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Based on the Financial Services Authority (OJK) No. 20/POJK.04/2016, Go Public companies listed on the Indonesia Stock Exchange (IDX) must submit annual financial reports that have been audited by independent auditors by the end of the fourth month within 120 days after the closing year ends. Therefore, the auditor needs sufficient time to gather evidence that can support them opinion. This study aims to obtain empirical evidence regarding the effect of profitability, solvency, audit committee, and audit quality on audit delay. The sample used in this study were 24 Property and Real Estate companies listed on the IDX as well as primary data (survey) at Public Accounting Firms taken in the attachments of journals and theses during the 2015-2019 period. The hypothesis test used is a multiple linear regression analysis with software eviews 12 version. The results of the study show that profitability (X1) and audit quality (X4) had a negative effect, solvency (X2) had a positive effect and the audit committee (X3) did not effect audit delay (Y). There is a significant increase in the average value every year.